Pathway analysis of genetic variants in folate‐mediated one‐carbon metabolism‐related genes and survival in a prospectively followed cohort of colorectal cancer patients. (29th May 2018) - Ose, Jennifer; Botma, Akke; Balavarca, Yesilda; Buck, Katharina; Scherer, Dominique; Habermann, Nina; Beyerle, Jolantha; Pfütze, Katrin; Seibold, Petra; Kap, Elisabeth J.; Benner, Axel; Jansen, Lina; et al.
Abstract: Folate‐mediated one‐carbon metabolism (FOCM) is a key pathway essential for nucleotide synthesis, DNA methylation, and repair. This pathway is a critical target for 5‐fluorouracil (5‐FU), which is predominantly used for colorectal cancer (CRC) treatment. A comprehensive assessment of polymorphisms in FOCM‐related genes and their association with prognosis has not yet been performed. Within 1, 739 CRC cases aged ≥30 years diagnosed from 2003 to 2007 (DACHS study), we investigated 397 single nucleotide polymorphisms (SNPs) and 50 candidates in 48 FOCM‐related genes for associations with overall‐ (OS) and disease‐free survival (DFS) using multiple Cox regression (adjusted for age, sex, stage, grade, BMI, and alcohol). We investigated effect modification by 5‐FU‐based chemotherapy and assessed pathway‐specific effects. Correction for multiple testing was performed using false discovery rates (FDR). After a median follow‐up time of 5.0 years, 585 patients were deceased. For one candidate SNP in MTHFR and two in TYMS, we observed significant inverse associations with OS ( MTHFR : rs1801133, C677T: HRhet  = 0.81, 95% CI: 0.67–0.97; TYMS : rs1001761: HRhet  = 0.82, 95% CI: 0.68–0.99 and rs2847149: HRhet  = 0.82, 95% CI: 0.68–0.99). After FDR correction, one polymorphism in paraoxonase 1 ( PON1 ; rs3917538) was significantly associated with OS (HRhet  = 1.28, 95% CI: 1.07–1.53; HRhzv  = 2.02, 95% CI:1.46–2.80; HRlogAdd  = 1.31, pFDR  = 0.01). Adjusted pathway analyses showed significant associations for pyrimidine biosynthesis ( P  = 0.04) and fluorouracil drug metabolism ( P  < 0.01) with significant gene–chemotherapy interactions, including PON1 rs3917538. This study supports the concept that FOCM‐related genes could be associated with CRC survival and may modify effects of 5‐FU‐based chemotherapy in genes in pyrimidine and fluorouracil metabolism, which are relevant targets for therapeutic response and prognosis in CRC. These results require confirmation in additional clinical studies. Abstract : Here, we present a comprehensive assessment of polymorphisms in FOCM‐related genes and their association with colorectal cancer survival with an additional assessment of interaction with 5‐FU‐based chemotherapy. This study supports the concept that FOCM‐related genes could be associated with CRC survival and may modify effects of 5‐FU‐based chemotherapy in genes in pyrimidine and fluorouracil metabolism, which are relevant targets for therapeutic response and prognosis in CRC. These results require confirmation in additional clinical studies.